2023
DOI: 10.4236/jdm.2023.131003
|View full text |Cite
|
Sign up to set email alerts
|

Risks Factors Associated with Diabetic Retinopathy at the National University Hospital Center Hubert Koutoukou Maga in Cotonou

Abstract: Diabetic retinopathy (DR) is one of the microvascular complications of diabetes. The aim of this study was to analyze the risk factors associated with the occurrence of diabetic retinopathy (DR) at the National University Hospital Center-Hubert Koutoukou MAGA (CNHU-HKM). Patients and method: this was a descriptive and analytical cross-sectional study with prospective data collection. It was carried out over a three-month period from July 10 to October 10, 2019. It concerned all patients suffering from diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is the leading cause of blindness in adults under 50, particularly in developed countries, and is among the five leading causes of visual impairment in all age categories [7]. In Benin, studies carried out in different medical centers have revealed an increasing prevalence of diabetic retinopathy, with figures varying between 17% and 43.33% [8][9][10]. Despite the availability of ophthalmological services for the management of diabetic retinopathy in Cotonou, several obstacles still limit access to care.…”
Section: Joj Ophthalmologymentioning
confidence: 99%
“…It is the leading cause of blindness in adults under 50, particularly in developed countries, and is among the five leading causes of visual impairment in all age categories [7]. In Benin, studies carried out in different medical centers have revealed an increasing prevalence of diabetic retinopathy, with figures varying between 17% and 43.33% [8][9][10]. Despite the availability of ophthalmological services for the management of diabetic retinopathy in Cotonou, several obstacles still limit access to care.…”
Section: Joj Ophthalmologymentioning
confidence: 99%